PENERAPAN STRATEGI BAURAN PEMASARAN ASURANSI SYARIAH DALAM MENDORONG MASYARAKAT MENJADI NASABAH: (Studi Pada PT. Asuransi Takaful Keluarga Cabang Palu) - Nur Wanita (ISTIQRA, 2017)
This research entitles the Application of Syariah Marketing Mix Assurance Strategy in increasing interest of people as customer (Case study on PT. Asuransi Takaful Keluarga Cabang Palu). The result of research shows that the application of marketing mix strategy by PT Asuransi Takaful Keluarga using 7 P, namely product, price, place, promotion, person, physical evidence and process strategy. Product strategy is applied by verification of product based on the people need which is consisting of individual and group assurance product. Individual assurance product consist of fulnadi product, takafulink salam cendekia, takafulink salam, and takafulink salam ziarah Baitullah. Even, the group assurance product consists of Takafulink product, Salam Comunity and Takaful Kesehatan Kumpulan Fulmedicare Gold. The prices offered are pretty affordable for the pople start from Rp. 200.000 until Rp. 350.000 with payment period in month, quarterly, and the first half and annual. Place strategy of PT. Takaful Keluarga Cabang Palu as agency service office that gives link to transact between customer and centre of PT. Asuransi Takaful Keluarga. Promotion strategy used agent which is directly monitoring and marketing of product. Then person strategy made a system through training and mentoring to motivate the agent to work professionally. In other, physycal evidence strategy provides infrastructure of management service agent and customer and also apply the accessibility of customer